Residential satisfaction and mobility behaviour among the young: insights from the post-Soviet city of Riga - Jānis Krūmiņš; Guido Sechi; Maris Berzins (Belgeo)
Urban residential areas in the former Soviet Union and Central Eastern Europe have experienced radical demographic and socioeconomic changes, with relevant consequences for residents. Although many studies have addressed post-socialist urban change at the macro level, little is known about individuals’ residential satisfaction. Besides, in this domain, two gaps must be acknowledged. First, most studies on residential satisfaction tend to focus on ‘static’ predictors, overlooking the interrelation of residential satisfaction with mobility behaviour, in spite of it being widely acknowledged in literature. Second, the analysis of residential satisfaction among specific socio-demographic groups tends to overlook younger residents in favour of groups which are considered to be more vulnerable.The aim of this study is to investigate how both mobility and static factors affect young individuals’ assessment of residential satisfaction. The research is based on 2015 panel survey data. The survey sample consists of around 700 permanent residents of Riga in the 15-34 age range. The findings suggest that residential satisfaction is significantly influenced, among other factors, by aspects of everyday mobility. In particular, our results highlight that transport modes and habits significantly affect residential satisfaction among younger residents, whereas they are negligible among elder ones.